The Use of Games Virus Hunter in Pandemic COVID-19 Against Development of Early Childhood - Apriloka, Dinita Vita; Suyadi, Suyadi; Na’imah, Na’imah (Indonesian Journal of Early Childhood Education Studies, 2020)
When this Indonesia was experiencing an outbreak of pandemic COVID-19, even the plague is happening not only in Indonesia but worldwide this is a challenge great for parents to keep the fruit of his heart that was not exposed to the virus is, in addition to the parents also become role important that should keep control of the growth and development of the fruit of this heart, especially in times of children early, which at the time these activities are limited so need a way to keep doing activities that can stimulate the growth and development of her with the good. The purpose of this study was to find out how the use of hunter virus game on child development and stimulate children when facing a COVID-19 pandemic, especially in the aspect of cognitive during the early childhood. In this study using qualitative methods with data collection techniques through observation, interviews, and documentation. Based on the result of observations and interviews with child game Hunter Virus This can be used as a media when the children are at home with the game this can introduce to the children about the virus that when this was happening. Besides, children with enthusiasm and are helped in learning about the dangers of the virus.